Rituximab for treatment of inhibitors in haemophilia A - Leissinger, Cindy; Josephson, Cassandra D.; Granger, Suzanne; Konkle, Barbara A.; Kruse-Jarres, Rebecca; Ragni, Margaret V.; Journeycake, Janna M.; Valentino, Leonard; Key, Nigel S.; Gill, Joan C.; McCrae, Keith R.; Neufeld, Ellis J.; Manno, Catherine; Raffini, Leslie; Saxena, Kapil; Torres, Marcela; Marder, Victor; Bennett, Carolyn M.; Assmann, Susan F. (Thrombosis and Haemostasis, 2014)
The development of antibodies against infused factor VIII (FVIII) in patients with haemophilia A is a serious complication leading to poorly controlled bleeding and increased morbidity. No treatment has been proven to reduce high titre antibodies in patients who fail immune tolerance induction or are not candidates for it. The Rituximab for the Treatment of Inhibitors in Congenital Hemophilia A (RICH) study was a phase II trial to assess whether rituximab can reduce anamnestic FVIII antibody (inhibitor) titres. Male subjects with severe congenital haemophilia A and an inhibitor titre ≥5 Bethesda Units/ml (BU) following a FVIII challenge infusion received rituximab 375 mg/m2 weekly for weeks 1 through 4. Post-rituximab inhibitor titres were measured monthly from week 6 through week 22 to assess treatment response. Of 16 subjects who received at least one dose of rituximab, three (18.8%) met the criteria for a major response, defined as a fall in inhibitor titre to <5 BU, persisting after FVIII re-challenge. One subject had a minor response, defined as a fall in inhibitor titre to <5 BU, increasing to 5–10 BU after FVIII re-challenge, but <50% of the original peak inhibitor titre. Rituximab is useful in lowering inhibitor levels in patients, but its effect as a solo treatment strategy is modest. Future studies are indicated to determine the role of rituximab as an adjunctive therapy in immune tolerisation strategies.Trial: “Rituximab for the Treatment of Inhibitors in Congenital Hemophilia A: The RICH Study. Registered as Clinical Trials.gov identifier- NCT00331006.
Keywords: Anti-CD20; antibodies; monoclonal; murine-derived; blood coagulation inhibitor; CD20 antibody; haemophilia A